Effective torsional stiffness of reinforced concrete structural walls - Luo, Da (2021)
When a structural wall is subjected to multi-directional ground motion, torsion-induced cracks degrade the stiffness of the wall. The effect of torsion should not be neglected. As a main lateral load resisting member, reinforced concrete (RC) structural wall has been widely studied under the combined action of bending and shear. Unfortunately, its seismic behavior under a combined action of torsion, bending and shear is rarely studied. In this study, torsional performances of the RC structural walls under the combined action is assessed from a comprehensive parametrical study. Finite element (FE) models are built and calibrated by comparing with the available experimental data. The study is then carried out to find out the critical design parameter affecting the torsional stiffness of RC structural walls, including the axial load ratio, aspect ratio, leg-thickness ratio, eccentricity of lateral force, longitudinal reinforcement ratio and transverse reinforcement ratio. Besides, to facilitate the application in practice, an empirical equation is developed to estimate the torsional stiffness of RC rectangular structural walls conveniently, which is found to agree well with the numerical results of the developed FE models.